THE ANALYSIS OF OVERLOAD VEHICLE DAMAGE FACTOR ON THE SERVICE LIFE OF THE PAVEMENT PLAN ON JALAN IMAM BONJOL, PONTIANAK - Kadarini, S. Nurlaily; Sumiyattinah, Sumiyattinah; Octaviana, Yanti; Hayu, Ertika (Fakultas Teknik Universitas Tanjungpura, 2024)
The overload offense hurts the highway. Namely, it lessens the remaining life on road pavement. Jalan Imam Bonjol has a primary collector road network; a segment of Jalan Imam Bonjol consists of 1 lane with two lanes and has a road width of 8 meters. This study aims to review the impact of vehicle overload on the percentage of overload, vehicle damage capacity (VDF) on flexible pavement, and design life of flexible pavement on Jalan Imam Bonjol with a simulation of increasing overload 20%-100% at 20% intervals. The method used to analyze the pavement design life is based on the cumulative ESAL results for each change in load weight. ADT data was obtained from a survey on Jalan Imam Bonjol in 2022. The study used the 1993 AASHTO method and the 2017 Bina Marga. From the calculation results in the 20th year, the W18 value for the plan is 461,656,4621 ESAL, and the W18 simulation overload value of 20% in the 20th year is 688,205,1963 ESAL. The increase in the value of W18 resulted in a decrease in the design life in the 17th year, namely the Ri value of -9.215%, and in the 20th year, the Ri value of 49.073%. In contrast, the Ri value in the 20th year was 0% under normal conditions, which could be interpreted As the vehicle being in average condition. The design life of the road that has been determined can last for the period of the plan that has been determined. Then, this study also considers adding the simulated overload to increase by 20%-100% with an interval of 20%, which decreases the design life. In the addition of a simulation load of 40%, the Ri value of -6.370% in the 13th year, at the addition of 60% excess load, the Ri value of -9.693% in the 10th year, the addition of 80% excess load, the Ri value of -1.418% in 7th, and the addition of 100% overload Ri value of -22,426 in the 6th year.